Structure of N-(1,3-benzothiazol-2-yl)-N-[1-(piperidin-4-ylmethyl)-4,5- dihydro-1H-imidazol-2-yl]amine, C16H21N5S - Yildirim, Sema Öztürk; Akkurt, Mehmet; Servi, Süleyman; Genç, Murat; Şekerci, Memet; Fun, Hoong Kun (Japan Society for Analytical Chemistry, 2006)
The crystal structure of N-(1,3-benzothiazol-2-yl)-N-[1-(piperidin-4-ylmethyl)-4,5-dihydro-1H-imidazol-2-yl]amine has been determined. The compound crystallizes in monoclinic P21/c; a = 11.7456(2)Å, b = 10.1254(2)Å, c = 13.9107(2)Å, ? = 104.669(1)°, V = 1600.46(5)Å3 and Z = 4. The final R value is 0.0483. The benzothiazol and imidazol rings are planar with the dihedral angle being 6.37(8)° between them. The piperidin ring takes a chair conformation. 2006 © The Japan Society for Analytical Chemistry.